Proceedings of the 23rd ACM Conference on Hypertext and Social Media 2012
DOI: 10.1145/2309996.2310005
|View full text |Cite
|
Sign up to set email alerts
|

Foundations of traversal based query execution over linked data

Abstract: Query execution over the Web of Linked Data has attracted much attention recently. A particularly interesting approach is link traversal based query execution which proposes to integrate the traversal of data links into the creation of query results. Hence -in contrast to traditional query execution paradigms-this does not assume a fixed set of relevant data sources beforehand; instead, the traversal process discovers data and data sources on the fly and, thus, enables applications to tap the full potential of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 20 publications
0
44
0
Order By: Relevance
“…Link traversal relies on the fact that if data are connected (through owl:sameAs, skos:exactMatch, rdfs:seeAlso or simply by vocabulary reuse), then one can naturally span datasources and gather new knowledge serendipitously. Various studies have shown that Linked Data can be traversed agnostically in contexts such as SPARQL query extensions [7] or (cor-)relation explanation [18,22]. So far, however, uninformed graph searches have been only used for Linked Data crawling or indexing [9,20].…”
Section: Related Workmentioning
confidence: 99%
“…Link traversal relies on the fact that if data are connected (through owl:sameAs, skos:exactMatch, rdfs:seeAlso or simply by vocabulary reuse), then one can naturally span datasources and gather new knowledge serendipitously. Various studies have shown that Linked Data can be traversed agnostically in contexts such as SPARQL query extensions [7] or (cor-)relation explanation [18,22]. So far, however, uninformed graph searches have been only used for Linked Data crawling or indexing [9,20].…”
Section: Related Workmentioning
confidence: 99%
“…For a semantic web query the finishing time also depends on factors such as delays caused by looking up URL (Uniform Resource Locators) [9], indexing large-scale of data [5], and dealing with query termination and broken links problems [10]. Some smart semantic search systems cannot illustrate their important performance in developing precision and lowering recall.…”
Section: B Efficiencymentioning
confidence: 99%
“…That is, to execute a given Linked Data query, live-explorationbased systems perform a recursive URI lookup process during which they incrementally discover further URIs that can be scheduled for lookup [25], [26], [27], [28], [29], [30]. Thus, such a system explores the WWW by traversing data links at query execution time.…”
Section: B Live Explorationmentioning
confidence: 99%